Kepemilikan Investasi Obligasi Perusahaan Perbankan di Indonesia: Dampak Penerapan PSAK 71 - Amrie Firmansyah; Meilynda Ahlam Matoviany (STIE Jambatan Bulan, 2021)
This study aims to review the impact of psak 71 implementation on banking companies that have financial investments, especially bond holdings. The method used in this study is qualitative method with content analysis. The data used in this study is secondary data in the form of financial statements of 6 banking sub-sector companies listed on the Indonesia Stock Exchange. This study concluded that accounting policies related to bond investments from 6 companies used in the study are valid since January 1, 2020, in accordance with PSAK 71